Asia Pacific Business Process Management Third Asia Pacific Conference, AP-BPM 2015, Busan, South Korea, June 24-26, 2015, Proceedings - Bae, Joonsoo; Suriadi, Suriadi; Wen, Lijie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the Third Asia Pacific Conference on Business Process Management held in Busan, South Korea, in June 2015. Overall, 37 contributions from ten countries were submitted. After each submission was reviewed by at least three Program Committee members, 12 full and two short papers were accepted for publication in this volume. These papers cover various topics and are categorized under four main research focuses in BPM: advancement in workflow technologies, resources allocation strategies, process mining, and emerging topics in BPM.
Advancement in Workflow Technologies -- Realisation of Cost-Informed Process Support Within the YAWL Workflow Environment -- A Cloud Workflow Modeling Framework Using Extended Proclets -- A Gateway-Centered Workflow Rollback-Points Ancestry Model for Sustainable Workflow Enactments -- jBPM4S: A Multi-tenant Extension of jBPM to Support BPaaS -- Resources Allocation Strategies -- An Efficient Resource Allocation Mechanism Based on Dynamic Pricing Reverse Auction for Cloud Workflow Systems -- On-the-Fly Performance-Aware Human Resource Allocation in the Business Process Management Systems Environment Using Naïve Bayes -- Algorithms for Process Analysis -- Run JTA in JTang: Modeling in Artifact-Centric Model and Running in Activity-Centric Environment -- TAR++: A New Process Model Similarity Algorithm Based on the Importance of TARs -- Process Mining -- Material Movement Analysis for Warehouse Business Process Improvement with Process Mining: A Case Study -- An Analytic Framework of Design for Semiconductor Manufacturing -- Workload and Delay Analysis in Manufacturing Process Using Process Mining -- Emerging Topics in BPM -- Social-Network-Based Personal Processes -- Discovering Information Diffusion Processes Based on Hidden Markov Models for Social Network Services -- Process Visualization Techniques for Multi-perspective Process Comparisons.
Keywords: Computer science; Management information systems; Industrial management; Data mining; Application software; Computer Science; Computer Appl. in Administrative Data Processing; Business Process Management; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Business Information Systems; Electronic books